Impact of COVID-19 on the Commodification of Bodo Foods with Special References to Sonitpur District of Assam - Anurag Hazarika; Thagi Ram Gogoi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2023)
In the twenty-first century, the globe has made major advancements in science, technology, medicine, travel, education, and practically every other aspect of existence. Living habits and interpersonal relationships have also changed as a result of these changes. On the other side, the arrival of the COVID-19 outbreak provoked a backlash against these changes. The epidemic has ruined small firms in addition to affecting socio-economic ties and advancement in many different professions. Even at the most basic levels, the pandemic had an impact on the manufacturers and retailers in Assam's smaller towns and districts. A community's identity was intended to be established through the introduction of ethnic food, which is also a cultural identity, as well as through the commercialization of Bodo ethnic food in order to generate income. Although there were limited economic benefits when commercialization first started, it did bring in money for those involved in this small business. But the Covid-19 outbreak and the ensuing lockdown have stopped people from purchasing and selling things, which has an impact on supply and demand as well as profit and loss. The overarching goal of the study is to examine the factors that affect small enterprises' economic revenue from Bodo ethnic culinary cuisines during the COVID-19 pandemic.